Pengaruh Komunikasi Organisasi dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai di Bagian Quality Assurance - Achmad Rozi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
The purpose of this study was to determine the effect on morale of organizational communication, to determine the effect on morale work environment and to determine the influence of organizational communication and work environment on morale. In conducting this research, the writer used quantitative descriptive analysis approach, namely by way of evidence collection information and other data necessary to then be processed and analyzed down to a conclusion. The population in this study were employees part of Quality Assurance and for a population of 41 employees. Engineering samples in this study probability sampling, the sample is calculated based on the formula Slovin, based on the results of these calculations by rounding the sample is assigned a total of 41 respondents. The results were obtained under the hypothesis 1 in this study organizational communication has a significant influence on employee morale tcount > t table (3.455> 2.023), while the correlation value obtained at 0.489 and have this level of contribution of the relationship is, it means the value organizational communication has increased the morale of employees will increase. Hypothesis 2 on the research work environment has a significant influence on employee morale tcount > t table (3.382> 2.023), whereas the correlation value of 0.481 and has a degree of contribution of the relationship is, it means the value of the work environment is getting better then the employee morale will be better anyway. Hypothesis 3 in this study organizational communication and work environment significantly affects employee morale obtained F count> F table (16.847> 3.245) it can be concluded that there is significant influence between organizational communication and the environment work on employee morale.